PENGARUH KESIAPAN BELAJAR TERHADAP PRESTASI AKADEMIK PADA SISWA DI ERA DIGITAL - Ika Suarsi (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This is a quantitative research with cluster random sampling. The purpose of this research is to determine the effect of student readiness on academic achievement, The independent variable in the study are student readiness while the dependent variables are academic achievement. The population in this study were all 236 students in class VIII SMP Negeri 2 Bulukumba, while the sample consisted of 106 students. Research data obtained through the scale and documentation of report cards. The data analysis technique is by multiple regression analysis. Based on the results of inferential statistics, the results of this research is partially student readiness does not affect academic achievement, in the digital era.